ISCHEMIA-MODIFIED ALBUMIN AND THYROID HORMONE LEVELS IN FIRST-TRIMESTER ABORTIONS: A RELATIONSHIP? - Barapatre, Amit R; rathod, Pallavi Anil; RATHOD, VENKATESH; Jadhao, Avinash Namdeo (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The objectives are to estimate maternal thyroid hormone levels and ischemia-modified albumin (IMA) levels in first-trimester pregnancy loss and to study the correlation between the maternal thyroid hormone levels and the IMA. Patients and Methods: We recruited 45 pregnant women with recurrent pregnancy loss (RPL) from our obstetric clinic as cases and 45 healthy pregnant women with the same gestational age and successful pregnancy outcomes as controls. Results: There is no correlation between the maternal thyroid hormone levels and the IMA levels in first-trimester pregnancy loss. Maternal IMA levels appear to be elevated in women with early RPL. Conclusion: In cases of first-trimester pregnancy loss, there is no association between maternal thyroid hormone levels and IMA levels. IMA cannot be used for the diagnosis and follow-up of early RPL because maternal IMA levels appear to be higher in women with early RPL.